STRATEGI PENINGKATAN MOTIVASI KERJA PEGAWAI MELALUI PENDEKATAN REWARD DAN PUNISHMENT PASCA PEMINDAHAN IBUKOTA (Studi Perpindahan Aktivitas Pemerintahan Di Provinsi Maluku Utara) - Armin Zakaria; Drs Nasrudin (Eqien - Jurnal Ekonomi dan Bisnis, 2017)
Sofifi's deciding as the capital of North Maluku-Province as to paragraph rule 9 verse 2 Invite Number 49 year 1999 about the Forming of North Maluku-Province, had gave in occupation Sofifi as government center. To to execute it constitutional obligation, the Government of North Maluku-Province must to move it government activity from Ternate to Sofifi. But policy the Government of North Maluku-Province mentioned its appear clapy beside hand because to its statement the Civil Country Employee yet ready and to undergo motivate descendant . The purpose of this study was to determine the cause of the Civil Servants Work Motivation North Maluku province tends to decrease after the transfer of the capital from Ternate to Sofifi and efforts to find out what will be done by the North Maluku provincial government in order to increase the motivation of civil servants North Maluku province after the transfer of the capital from Ternate to Sofifi. In this study, the writer used descriptive qualitative approach. The data was collected through interviews and documentation using probability sampling techniques were allotted to civil secretariat North Maluku province. From the results of research and discussion, the authors conclude that there are several factors that cause decreased motivation of civil servants working in North Moluccas province after relocation of the capital from Ternate to Sofifi including transport factors, weather factors, factors shelter and clean water factor. The attempts that will be made by the Provincial Government of North Maluku improve the motivation of civil servants in the province of North Moluccas after the transfer of the capital from Ternate to Sofifi among other allowances, provision of housing facilities, provision of clean water, provision of information and communication technology facilities, provision of rewards and penalties to civil servants North Moluccas province that was not disciplined.